Structure of Health Care System: Vital in Promoting Community Well-Being (International Journal of Preventive Medicine and Health (IJPMH), 2024)
It is understood on a comprehensive basis that individuals, belonging to all occupations, communities, and socio-economic backgrounds are overwhelmed by different types of health problems and illnesses. These are experienced in a major or minor form. The research studies have indicated that in rural communities, the individuals are depending on the natural environmental conditions in order to treat various types of health problems and illnesses. But there are formulation of programs, which are putting emphasis on bringing about improvements in health care services within rural communities. On the other hand, within urban communities, the medical and health care services are in a well-developed condition. The individuals employed in these are required to be well-versed in terms of job duties and responsibilities. Furthermore, the different types of methodologies and procedures are required to be put into operation in a satisfactory manner. As a consequence, individuals are rendering an important contribution in promoting good health, physically as well as psychologically. One of the important aspects that needs to be taken into account is, individuals are required to prepare themselves adequately in making sure, individuals are benefitting from the services. Therefore, it is well-understood, structure of health care system is vital in promoting community well-being. The main concepts that are taken into account in this research paper are, the health care system in rural areas, functioning of community health care centres, functioning of primary health care centres, functioning of sub-centres and measures to be implemented in bringing about improvements in structure of health care system.